Answer:
D. 25
Step-by-step explanation:
16 divided by 64% is 25
I thank its A if not I’m sorry
Answer:
A
Step-by-step explanation:
We have the two functions:
![f(x)=-4x+3\text{ and } g(x)=3x^2+2x-4](https://tex.z-dn.net/?f=f%28x%29%3D-4x%2B3%5Ctext%7B%20and%20%7D%20g%28x%29%3D3x%5E2%2B2x-4)
And we want to find (f+g)(x).
Note that this is the same thing to f(x)+g(x). Therefore:
![\begin{aligned} (f+g)(x)&=f(x)+g(x) \\ &=(-4x+3)+(3x^2+2x-4) \end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%20%28f%2Bg%29%28x%29%26%3Df%28x%29%2Bg%28x%29%20%5C%5C%20%26%3D%28-4x%2B3%29%2B%283x%5E2%2B2x-4%29%20%5Cend%7Baligned%7D)
We simply substituted them for their equations.
Simplify. Combine like terms:
![=(3x^2)+(-4x+2x)+(3-4)](https://tex.z-dn.net/?f=%3D%283x%5E2%29%2B%28-4x%2B2x%29%2B%283-4%29)
Add:
![=3x^2-2x-1](https://tex.z-dn.net/?f=%3D3x%5E2-2x-1)
Hence, our answer is A.
Answer:
my guess would be 3.52
Step-by-step explanation: